Location as the reason for the problems of old industrialised settlements - Raigo Ernits (European Journal of Spatial Development, 2021)
In this paper we will chart the problems of small single-company (so called monofunctional) industrial settlements in post-socialist Estonia. The major research question asked will thus be whether the disadvantageous location of these industrial plants is the reason for problems in such settlements. Using the notion of gravity models we will calculate the distance factors of such settlements in relation to larger centres, and compare them across different groups of different kinds of settlements. The conclusion arrived at is that advantageous location (location close to a larger centre) is a necessary though not a sufficient condition for guaranteeing the development and success of settlements. The main determinant factors in the success of a settlement are the fulfilment of the conditions for a good social and economical environment, while it is undoubtedly the case that a healthy environment favouring the growth and deployment of entrepreneurial skills develops more easily in settlements located nearer to larger centres.